Um estudo sobre as principais acusações e defesas sobre antissemitismo e omissão de Pio XII nos episódios da Shoah - Souza, Luiz Tarciso (2013)
The present dissertation is a study about the controversy established posthumously to Pius XII in regard to his attitudes in face of Shoah's episodes the annihilation of six millions Jews during the Second World War. Starting from the primary sources and a selected bibliography, this research sought to follow the facts and, mainly, to evaluate the counterpoised claims by several authors about Pius XII's actions and words. Some authors accuse him of silence and omission about the fate of the persecuted Jews by the Nazis, because of an alleged anti-Semitism that they identified on the pontiff. However, others authors defend and legitimate him, claiming that Pius XII strictly followed the neutrality of the Vatican, adopting an impartiality posture and prudent reserve to avoid greater evils to the victims. Instead of harsh words condemning the Jew s genocide, he chose to promote the rescue of victims who were preserved from deportation to the extermination camps and sheltered by clerics and religious in several ecclesiastical institutions including the Vatican itself and its extraterritorial properties. As a result, the research allowed us to evaluate the arguments of Pius XII's defenders as the most consistent in face of the available evidences, especially considering the favorable and widely documented statements from contemporary Jewish persons and institutions to the facts in dispute. However, this research also allowed us to notice that there are some gaps to be filled before definitely solve this controversy something that perhaps just becomes viable with the fully opening of the Vatican archives and the archives of the other governments and chancelleries that were involved in this issue